Answer:
see explanation
Explanation:
Expand the right side and then compare like terms with the left side.
(q + 2
)²
= q² + 4q
+ 12
= q² + 12 + 4q
![√(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/3jkdozb6pk3x1px4ym8d058os0wzvynm5a.png)
Compare like terms with 28 + p
![√(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/3jkdozb6pk3x1px4ym8d058os0wzvynm5a.png)
Comparing the
terms gives
p = 4q
and comparing the constant terms gives
q² + 12 = 28 ( subtract 12 from both sides )
q² = 16 ( take the square root of both sides )
q = ±
= ± 4
Hence
p = 4q = 4 × ± 4 = ± 16